Fresh state properties and compressive strength development of reactive MgO-based systems - Taj, Khalilullah; Akturk, Busra; Ulukaya, Serhan (ELSEVIER, 2022)
In this study, flowability, setting time, and strength gain of mortars containing reactive magnesium oxide cement (RMC) and a combination of micro-silica (MS), nano-silica (NS), slag, and fly ash (FA) as precur-sors without employing accelerated carbonation have been investigated. To increase the flowability and hydration degree, sodium hexametaphosphate (SHMP) was incorporated. The series containing RMC and MS simultaneously, had the greatest 3-day compressive strength value of about 25 MPa, whereas further strength gains in all the mixtures until the 7th day was minimal, which establishes that strength gains were due to hydration degree, not carbonation. RMC and MS simultaneously in a series, a combination of extremely high fineness materials dropped the flowability; the presence of slag and FA, on the other hand, enhanced it. The inclusion of NS in the mix didn't demonstrate a perceptible change in any of the properties measured in this study; its inertness could be attributed to the unsuitable dispersion method. Setting time of reference mix was the shortest, which was in conformity with its fast initial strength gain. Replacement of RMC with any other binder extended both the initial and final setting time. It was hypothesized that a major difference in this study is the use of SHMP as a dispersant and hydration agent. The outcomes of this study confirm that RMC can be a potential binder material to be used in mor-tar productions.Copyright (c) 2022 Elsevier Ltd. All rights reserved.Selection and peer-review under responsibility of the scientific committee of the International Confer-ence on Advances in Construction Materials and Structures.
Keywords: Reactive magnesium cement; Micro-silica; Nano-silica; Strength gain; ACCELERATED CARBONATION; CEMENT PASTES; PERFORMANCE; CONCRETE; MICROSTRUCTURE; HYDRATION; MIXTURES; BINDERS; MORTAR; SILICA; Materials Science